Simultaneous extraction and determination of 34 multiclass endocrine disrupting compounds in river water using solid-phase extraction coupled with three liquid chromatography–mass spectrometry methods - Muhammad Raznisyafiq, Razak; Wee, Sze Yee; Didi Erwandi Mohamad, Haron; Norbaya, Hashim; Nasehir Khan E.M., Yahaya; Nirmala Devi, Kerisnan (Kerishnan); Raja Baharudin Raja, Mamat; Ahmad Zaharin, Aris (Elsevier B.V., 2025)
Endocrine-disrupting compounds (EDCs) encompass a diverse range of substances found in river water, and can have significant impacts on aquatic organisms and human health. In this study, a multiresidue analytical method was developed for determining 34 endocrine-disrupting compounds (EDCs), including pharmaceuticals, plasticizers, and hormones by utilizing a dual-cartridge solid-phase extraction (SPE) approach (Phenomenex® Strata-X and Oasis WAX) coupled with liquid chromatography–tandem mass spectrometry (LC–MS/MS). The optimized method achieved >70 % recovery for all analytes, demonstrating robust extraction efficiency. The reliability and robustness of the optimized method were ensured through meticulous validation procedures encompassing linearity, precision, recovery, limit of detection (LOD), and limit of quantification (LOQ). The method demonstrated satisfactory performance overall, meeting established precision levels and exhibiting LOD and LOQ values ranging from 0.1 ng/L to − 50 ng/L and 0.3 ng/L–200 ng/L, respectively. The linearity of the compounds indicated strong regression, with a goodness of fit (r) exceeding 0.99 for all targeted compounds. Satisfactory precision was achieved with a relative standard deviation (RSD) less than 18 %. However, two compounds showed lower precision during LC–MS/MS analysis, notably atenolol (21.97 %) and diltiazem (34.28 %). The validated method was used for the quantitative EDCs analysis of river water samples collected from five locations within the Langat River, Malaysia. Application of this method to real water samples from the Langat River revealed the presence of various EDCs, even upstream, underscoring the pervasive nature of EDC contamination in freshwater environments. This study contributes to the advancement of analytical chemistry methodologies for the comprehensive assessment of EDC occurrence in environmental waters, thereby facilitating informed decision-making processes for pollution control and public health protection.